Treating agnosic alexia complicated by additional impairments - Francis, DR; Riddoch, M; Humphreys, G (2001)
In this paper we present a cognitive analysis and therapy study of a patient, MGM, who was alexic due to a profound visual agnosia. Our analysis indicates that the patient had impaired processing of multiple form elements, and impaired verbal memory, along with relatively good phonological skills. A set of therapies was introduced in which MGM was taught (1) to identify letters, (2) to link letters to phonemes, (3) to blend consonant clusters, and (4) to use a verbal compensatory strategy to read irregular words. We demonstrate that the therapy was successful in helping MGM to read. We discuss the results in the light of arguments about the utility of cognitive approaches to therapy.